The influence of gelatine on the corrosion behaviour of cold worked copper wire in alkaline media - Ivanov Svetlana; Rajčić-Vujasinović Mirjana; Stević Zoran (Journal of Mining and Metallurgy. Section B: Metallurgy)
Copper wire obtained by dip-forming process was cold worked to the deformation degrees of 83, 87, 91, 95 and 99 %. Electrochemical potentiodynamic method was used to investigate corrosion behavior of these wires in aqueous solutions of Na2CO3 (1 mol/dm3). Open circuit potentials as well as peak potentials are given as a function of deformation degree in Na2CO3 without and with addition of gelatine in concentration between 0.1 and 0.5 g/l. It was found that the addition of gelatine does not change the mechanism of the process, but influences on current density. Small concentrations of gelatine (0.1 g/l or less) have positive influence on the corrosion protection of copper in alkaline solution, but the addition of gelatine in concentration 0.5 g/l causes the increasing of its corrosion rate.